Approaching Culture through Humour in the EFL Classroom : at the Department of Letters and English, University of Frères Mentouri Constantine1 - MAHCENE , Sarra (Journal of Human Sciences, 2020)
Teaching a language as a system outweighs its cultural underpinnings which enfold a large amount of what is said. This calls for a reconsideration of the way of teaching so as to give culture its weight. Over seriousness in classrooms tends to fan the flame of tension and anxiety among students; consequently, classrooms should be designed with an appealing atmosphere that encourages the learning process and impedes boredom. To this end, humour makes a convenient teaching method which both eliminates boredom, and stimulates culture learning. Thus, the aim of this paper is to get an insight into students' willingness to study culture through the humorous tunnel. A descriptive study relying on a questionnaire, as a research tool, is used to see the validity of humour in the classroom. The questionnaire is addressed to a sample of 46 second year students extracted from a population of about 250 students at the Department of Letters and English, University of Frères Mentouri, Constantine 1. Findings reveal that humour is worth incorporation in the EFL classroom because it both generates a cosy, stress-free atmosphere and helps to learn about the target culture.